Importance analysis of evaluation items in memorial space planning: enhancing tourism experiences through phenomenological spatial perspectives - Jiaxing Liu; Jue Chen; Yongchao Zhu; Lie Zhang (Journal of Asian Architecture and Building Engineering)
This study introduces a novel spatial planning evaluation method that employs a phenomenological spatial perspective to enhance the dark tourism experience in memorial spaces. The phenomenological view recognizes space as a comprehensive entity and emphasizes the impact of perception and behavior on the experiential aspect of space. First, a theoretical exploration was conducted to establish the connections among memorial spaces, dark tourism, and phenomenology. Subsequently, a set of spatial evaluation elements and detailed indicators were developed. Finally, the analytic hierarchy process was applied to determine each hierarchical element’s importance and assign weights to the evaluation indicators. The findings highlight the significance of perceptual and behavioral factors in the dark tourism experience within memorial spaces. Thus, these elements should be considered when designing new projects or undertaking functional renovations in such spaces.